Seasonal and habitat-wise variations of creek water particulate and dissolved organic carbon in arid mangrove (the Persian Gulf). (1st August 2018) - Ray, R.; Weigt, M.
Abstract: The present study examines the effect of mangrove vegetation and different seasons on organic carbon pools, distributions, and source compositions under the stressed hydro-climatological settings of the Iranian coast (Persian Gulf). Significant seasonal and spatial differences were detected only for the δ 13 POC (particulate organic carbon) owing to the fluctuation of its sources. Five end-member particulate organic carbon sources (POC) (mangrove leaf, planktonic particles, zooplankton, microphytobenthos (MPB), and sediment) contributed to the POC pool at different levels depending on their seasonal and site-specific abundance. Variations in topographic features such as, the elevations of mangrove and non-mangrove creeks, appeared to play an important role in regulating POC concentrations but not DOC concentrations. Planktonic particles contributed to the POC pool (maximum 10–65%) at the mangrove sites mostly in the summer whereas the contributions of sediment and MPB (5–35%) increased in winter. Iranian mangroves are weak exporters of carbon to the Persian Gulf where mangrove plant materials (leaf, litter) had little contributions to the POC and DOC pool (5–25% and 8–15%, respectively). It is most likely that OC export in these arid regions are limited by low rainfall and river input. Finally, seasonality and site-specific activity largely control OC dynamics in these relatively understudied arid mangroves. Highlights: Source compositions of OC are determined for the Iran mangroves. Variations of POC and isotopes are strongly season dependent. Iranian mangroves are weak exporter of POC. Low discharge and rainfall reduce OC export from the mangroves.